A Fold Bifurcation Theorem of Degenerate Solutions in a Perturbed Nonlinear Equation - Ping Liu; Yuwen Wang (Abstract and Applied Analysis)
We consider a nonlinear equation F(ε,λ,u)=0, where the parameter ε is a perturbation parameter, F is a differentiable mapping from R×R×X to Y, and X, Y are Banach spaces. We obtain an abstract bifurcation theorem by using the generalized saddle-node bifurcation theorem.